Pengaruh Marketing Mix Terhadap Keputusan Pembelian KPR Subsidi Yang Dimoderasi Oleh Kualitas Pelayanan - Dalimunthe, Selli Askia; Rino, Rino (Universitas Negeri Padang, 2024)
The research aims to evaluate the impact of the marketing mix on the decision to purchase subsidized mortogages (KPR) at PT. Mandiri Adna Properti, with service quality as a moderating variable. The study is causal in nature and involves customers of PT. Mandiri Adna Properti . A simple random sampling method was used, with a total population of 86 customers. From this population, a sample of 71 customers was selected. The criteria for inclusion were customers who had made a purchase decision at the company. Both primary and secondary data were used. Primary data was obtained through questionnaires distributed to buyers at PT. Mandiri Adna Properti, while secondary data was obtained from reference books and websites. SmartPLS 4.0 software was used to conduct SEM analysis. The results showed that (1) Product has a significant influence on purchase decisions; (2) Price also has a significant influence on purchase decisions; (3) Location has a significant influence on purchase decisions; (4) Promotion does not influence purchase decisions; (5) Product has a significant impact on purchase decisions when moderated by service quality; (6) Price, when moderated by service quality, has a significant impact on purchase decisions; (7) Location, when moderated by service quality, has a significant impact on purchase decisions; and (8) Promotion, when moderated by service quality, does not significantly influence purchase decisions.